Determinants of Effective E-Procurement System: Empirical Evidence from Indonesian Local Governments - Nani, Dhiona Ayu; Ali, Syaiful (Jurnal Dinamika Akuntansi dan Bisnis, 2020)
This study investigates the effect of the strategy-technology-organization-people-environment (STOPE) variables on the effectiveness of e-procurement implementation in improving accountability, transparency, efficiency, and effectiveness of local governments in Indonesia. The population of this study is local government procurement services (or LPSE) in Indonesia. The sample, 96 LPSE, was selected using simple random sampling method. The data was collected through questionnaires distributed via email to 289 LPSE. The respondents were 33 managers and 63 information technology professionals of local government procurement services (33% response rate). Partial least squares (PLS) was used to analyze the data and test the hypotheses. The findings showed that strategies, objectives, integration between organizations and systems, and human resource assistance can improve the accountability, transparency, efficiency, and effectiveness of the government in implementing procurement activities